NUOVA OFFICINA ASSERGI: a novel infrastructure for the production of cryogenic and radiopure Si-based photodetectors - Consiglio, L.; Flammini, A.; Ianni, A.; Marasciulli, A.; Panella, G.; Pietrofaccia, L.; Sablone, D.; Tartaglia, R. (Frontiers in Physics, 2024)
The NUOVA OFFICINA ASSERGI (NOA) is a new facility for the production and integration of large-area silicon photodetectors operating at cryogenic temperatures. Silicon photomultipliers are proving to be a promising technology for next-generation experiments searching for rare events in underground laboratories. New photosensor technology with high performance at cryogenic temperature has been developed by Fondazione Bruno Kessler (FBK) and integrated at Laboratori Nazionali del Gran Sasso (LNGS) into large-area optical units, thus opening the frontiers toward the realization of scalable liquid argon experiments probing dark matter. The massive production of such detectors is now feasible in NOA, a clean room of 421 m2 designed to operate in a radon-free mode. NOA, commissioned and operational at LNGS, hosts the most advanced packaging machines and electronic test facilities for the integration of silicon devices in a dust-controlled environment. The infrastructure layout is split into two experimental areas: one for the production of electronic devices and cryogenic temperature tests and the other for operating with large detector installations. The NOA facility can be operated with a radon abatement system, making it a unique facility for packaging and testing SiPM-based photosensors and for assembling detector components in a radon-free environment. Therefore, NOA supports the deployment of underground experiments at LNGS and the development of new technologies for the search of rare events, such as dark matter and neutrinoless double-beta decay.